Effects of Music Therapy Combined with Habit Reversal Training on Children with Tic Disorders: A Retrospective Study - Yali Liu; Haixia Chang; Xiulin Li; Mingjing Zhang; Xia Wang (Noise and Health)
Objective This study aimed to investigate the effects of music therapy combined with habit reversal training (HRT) on children with tic disorders. Methods: A retrospective study was conducted on the clinical data of 122 children diagnosed with chronic tic disorders admitted to Hebei Children’s Hospital Affiliated to Hebei Medical University from January 2021 to January 2024. According to different treatment methods, patients were separated into the HRT group (n = 55), who received routine HRT, and the music therapy group (n = 67), who received music therapy combined with HRT. The baseline data before treatment and the clinical efficacy after 8 weeks of treatment of the two groups were compared. Before and after the 8-week treatment, the Yale Global Tic Severity Scale (YGTSS) scores, serum neurotransmitter levels, Child Behavior Checklist (CBCL), and Pediatric Quality of Life Inventory (PedsQL) were compared between the two groups. Results: After an 8-week treatment, the Global Severity Score and Total Tic Score of YGTSS significantly decreased in both groups, with the music therapy group showing lower scores than the HRT group (P < 0.05). The total effective rate in the music therapy group was higher than that in the HRT group (92.54% vs. 80.00%, P < 0.05). Serum dopamine and serotonin levels significantly decreased after treatment in both groups, with the music therapy group showing lower levels than the HRT group (P < 0.05). Conversely, serum γ-aminobutyric acid levels significantly increased after treatment in both groups, with the music therapy group showing higher levels than the HRT group (P < 0.05). The CBCL and PedsQL scores significantly improved after treatment in both groups, with the music therapy group showing a significant decrease in CBCL scores and a significant increase in PedsQL scores compared with the HRT group (P < 0.05). Conclusion: Music therapy combined with HRT significantly enhanced treatment efficacy for children with tic disorders. It reduced tic severity, improved behavioral outcomes, and modulated neurotransmitter levels. The study demonstrated the potential clinical value of music therapy as a nonpharmacological treatment for tic disorders.